Solution of A P and S wave propagation model using high performance computation (2019)
The propagation of seismic waves is affected by the type of transmission media. Therefore, it is necessary to solve a differential equation system in partial derivatives allowing for identification of waves propagating into an elastic media. This paper summarizes a research using a partial differential equation system representing the wave equation using the finite differences method to obtain the elastic media response, using an staggered grid. To prevent reflections in the computational regions, absorbent boundaries were used with the PML method. The implementation of the numerical scheme was made on two computational architectures (CPU and GPU) that share the same type of memory distribution. Finally, different code versions were created to take advantage of the architecture in the GPU memory, performing a detailed analysis of variables such as usage of bandwidth of the GPU internal memory, added to a version that is not limited by the internal memory in the graphic processing unit, but rather by the memory of the whole computational system. © 2019 Ecopetrol S.A.. All rights reserved.